Comparison of outsourced operations in wood procurement in Finland and Slovakia - Ambrušová, Lucia; Marttila, Juhani (Finnish Forest Research Institute, 2012)
The majority of wood procurement in Europe is conducted by forestry contractors. Thus, the conditions for contractor services vary significantly in diffent regions. The objective of this paper is to describe the outsourced operations in wood procurement in Finland and Slovakia.Forest machinery and timber haulage are driven mostly by small enterprises in both countries. However, the contractual relations differ significantly. In Finland, forest industry companies generally buy their timber as standing sales and arrange harvesting and transportation with different contractors. Forest harvesting contractors have been responsible for industrial roundwood harvesting for more than 40 years. The biggest customer groups are large industry companies and state forests.In Slovakia, fundamental changes took place in the forest sector in the early 1990s. Nowadays, forest owners typically sell wood to their customers and contract separately with contractors. In general, contractors try to offer as complex a range of services as possible (harvesting, silviculture, transportation, etc.). There are major differences in the amount of harvested timber and the structure in private holdings in these countries. Also, the level of mechanisation differs widely. Nearly all felling in Finland is conducted mechanically by harvesters. In Slovakia, most enterprises carry out manual harvesting operations.
Layout: Anne Siika/Metla
Keywords: Slovakia; Suomi; puunhankinta; puunkorjuu; ulkoistaminen; Finland; harvesting; outsourcing; Slovakia; wood procurement